Pengaruh Penerapan Terapi Ankle Pump Exercise Dengan Elevasi Kaki 30 ̊ Terhadap Edema Kaki Pada Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa - Armila Damayanti; Resti Yuliati Sutrisno; Purnomo Widiyanto (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Chronic Kidney Failure (CKD) is a kidney disease caused by damage or dysfunction in the kidneys. A common problem in CKD sufferers is excess fluid which causes swelling in the extremities (edema). The causes of edema in CKD patients are failure to comply with fluid restrictions, lack of dietary control, fluid and sodium retention. One of the independent nursing interventions that is very effective for treating edema is ankle pump exercise therapy with leg elevation at 30 ̊. The case study was carried out in the hemodialysis unit at Dr. Tjitrowardojo Purworejo. The aim of the study was to identify the effect of providing ankle pump exercise therapy and 30° leg elevation intervention to reduce edema in CKD patients. The research design used is a descriptive method with a case study approach. The subjects of this case study are CKD patients undergoing hemodialysis who experience edema and patients who have signed an informed consent form. The instrument used is a monitoring sheet for the degree of edema. The intervention given in this case study was ankle pump exercise therapy and 30° leg elevation which was carried out for 7 minutes in 3 meetings over 7 days. Evaluation was carried out on days 1, 4, 8. The results showed that the degree of edema on the first day was grade III (5mm), on the second day it was grade II (4mm), on the third day it was grade I (2mm). Based on the results of the case study, it can be concluded that the application of ankle pump exercise and 30° elevation has proven effective in reducing the degree of edema in chronic kidney failure, so that this independent nursing intervention can be carried out by nurses for CKD patients undergoing hemodialysis.